Optimalisasi Pola Usahatani Lahan Rawa Lebak Di Kawasan Pemulutan Kabupaten Ogan Ilir Sumatera Selatan - Siska Tri Wulandari; Aliyah Aliyah; Rabecha Maros Framita (Universitas Wahid Hasyim, 2025)
Abstract The area of fertile land for food crops, especially rice, is decreasing. Suboptimal land is an alternative available to the government to achieve the target of food self-sufficiency, especially rice. One of the suboptimal lands that is still very large (around 20 million hectares) is swamp land (tidal or lowland). The Pemulutan area of Ogan Ilir Regency, South Sumatra is a suboptimal agricultural area with a lowland land typology. In this area, rice farming activities carried out by farmers can only be carried out once a planting season each year. This results in the income obtained by farmers not reaching the maximum due to the suboptimal farming patterns used by farmers. The objectives of this study are 1). Determining the optimal farming pattern in the use of swamp land so that farmers' income can be maximized, 2) Analyzing the effect of changes in the availability of farmer resources on the optimal farming pattern that should be implemented and, 3) Revealing the problems faced by rice farmers in the swamp land of the Pemulutan Area, Ogan Ilir Regency in implementing optimal farming patterns. The analysis method used is a linear programming model, which will then be processed using the ABQM computer program. The results of this study are expected to be information and consideration for local farmers in choosing the farming pattern that they will manage, for the government as information and consideration in determining and formulating new policies, especially regarding the development of swamp land in South Sumatra, and scientific aspects as additional information specifically for those interested in conducting research in swamp land. Keywords: Farming; Swamp Land; Optimization; Pattern; Farmers